A note on linear θ-derivations on JB∗-triples - Zeinab M. Abd EL-Kader; Adel M. Zaki; Reham M. Esmail (Journal of the Egyptian Mathematical Society, 2011)
In this paper we prove a generalization of the stability of the functional equation in the spirit of Hyers, Ulam and Rassias. Also we introduce the concept of linear θ-derivations on JB∗-triple, and prove the generalization of the stability of the functional equation in the spirit of Hyers, Ulam and Rassias of linear θ-derivations on JB∗-triple. For resent results see [1–3].